OPTIMALISASI KERJA KELOMPOK UNTUK MENINGKATKAN KETERAMPILAN GURU DALAM MENGGUNAKAN MEDIA PEMBELAJARAN DI TK NEGERI PEMBINA MEDANG KAMPAI DUMAI - Aida (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This article discusses teachers’ low skills in using instructional media at the Public Kindergarten of Pembina Medang Kampai Dumai. Hence, it requires action to overcome this problem, one of them is to apply group work. Based on the background description in the identification and limitation of the problem, this research focused on improving teacher skills in applying instructional media. The type of research is school action research (PTS), which identifies the improvement of teacher skills in applying instructional media in teaching through group work at Public Kindergarten of Pembina Medang Kampai Dumai Public Kindergarten. Based on the results of the data presentation and discussion, the implementation of group work can improve teacher skills in applying learning media at the Public Kindergarten of Pembina Medang Kampai Dumai Public Kindergarten. It is proven from the research findings in the pre-test, the average teacher’s skill in applying instructional media is only 40%. After applying the group work in Cycle I, the teachers’ skills in applying instructional media increased to 54%. After revising the group work in cycle II, the teacher's skills in applying instructional media increased to 83%. Thus, the implementation of group work can improve teacher skills in applying instructional media at the Public Kindergarten of Pembina Medang Kampai Dumai.